Efeitos da prática espaçada e da prática massiva na aquisição e retenção de um pequeno vocabulário emergente em segunda língua - Silva, Luísa Moreira Messias Vieira da (Universidade Federal de São Carlos, 2025)
This study compared the effects of tact instruction with spaced practice versus tact instruction with massed practice on the acquisition and retention of directly taught vocabulary and emergent vocabulary (native-to-foreign and foreign-to-native intraverbal responses). Six undergraduate students whose native language was Portuguese and who had no prior exposure to the target language (Korean) participated. The experiment was conducted online and synchronously, using a multiple-probe design across participants. Twenty different Korean words were organized into two sets of 10 stimuli each. Half of the participants first learned one set of stimuli using spaced practice and then another set using massed practice. The remaining participants were exposed to the reverse order. Pretest sessions assessed Korean tact responses and bidirectional intraverbal responses between the native and foreign languages prior to instruction. In the massed practice tact instruction condition, 24 Korean tact instruction blocks were conducted in a single day. In the spaced practice tact instruction condition, 24 Korean tact instruction blocks were distributed across three applications of eight blocks each, implemented every seven days. The first posttest for each condition occurred immediately after the presentation of the final training block. Follow-up sessions were conducted 30 and 60 days after instruction in each condition. The results indicated that both types of practice produced high percentages of accuracy in tact and intraverbal responses immediately following instruction. However, spaced practice produced greater retention of both directly taught and emergent responses compared to massed practice, confirming and extending previous studies on the topic.
Effects of spaced practice and massed practice on the acquisition and retention of a small emergent second-language vocabulary
Keywords: Ensino de tato; Prática espaçada; Prática massiva; Respostas emergentes; Retenção; Segunda língua; Tact instruction; Spaced practice; Massed practice; Emergent responses; Retention; Second language; CIENCIAS HUMANAS::PSICOLOGIA; 4. Educação de Qualidade